Avaliação do dano ao DNA em pacientes com doença renal crônica submetidos à hemodiálise e sua associação com o metabolismo do ferro e estresse oxidativo - Cichota, Luiz Carlos (2016)
Chronic kidney disease (CKD) is a condition in which the kidneys lose their ability to perform basic functions. Hemodialysis is the most commonly used alternative treatment for these patients, however, it exposes these individuals to oxidative stress, which is an importante risk factor for DNA damage. The decrease in functional capacity of the kidneys can trigger serious health problems for these patients, such as anemia, which has significant impact on their quality of life and needs to be corrected with adjuvant therapy, primarily intravenous iron. However, iron is an oxidative metal that enhances the oxidative stress, which may result in an increase in DNA damage. Thus the aim of the study was to investigate the association between iron metabolism, oxidative stress and free circulating DNA in patients with renal disease undergoing hemodialysis. Iron levels, ferritin, transferrin, total antioxidant capacity (TAC), the total oxidant status (TOS) and Albumin modified by ischemia (AMI) and damage DNA in the test Picogreen® were measured in forty CKD patients undergoing hemodialysis and forty control subjects. We observed that the DNA damage was significantly elevated in patients with CKD undergoing hemodialysis when compared to the control group. Furthermore, we demonstrated an association between the increase in DNA damage in the CKD with serum ferritin levels and decreased glomerular filtration rate (GFR). We also noticed that a single hemodialysis session did not increased DNA damage. Moreover, this study also found out that patients with CKD undergoing hemodialysis who used intravenous iron therapy had higher circulating free DNA levels than those who did not use therapy with iron. In this study, we also observed that patients who used intravenous iron therapy had a decrease in antioxidant levels (TAC) and a significant increase in oxidant levels (TOS and IMA). Thus, we speculate that the events that affect patients with CKD, such as an increase in the stock of iron, declining renal function, oxidative imbalance and treatment with intravenous iron may be factors that directly contribute to increased DNA damage.